Fostering Inclusive Education in Asia: Insights from a Systematic Literature Review - Nurul Huda, Ibrahim; Nazmin, Abdullah; Mohd Fairuz, Jafar (INTI International University, 2024)
The strong communication strategies for inclusive education policies are intended to offer equality across the board for access to education for all students, including those with special needs. This systematic review used ROSES (Reporting Standards for Systematic Evidence Syntheses) methodology to investigate the use of communication strategies for inclusive education by countries in Asia. The articles were based exclusively on these three databases in conjunction with Google Scholar: Scopus, ProQuest, and ERIC, subjected to a series of screening, data collection, and evaluation of quality processes as guided by ROSES protocols. Criteria for inclusion included research on events on communication strategies regarding policy concerning inclusive education in Asia. Themes that emerged included the negotiation of partnerships, channels for communication, and cultural sensitivity. The paper identifies communication strategies that are culturally and contextually relevant towards the successful implementation of inclusive education policies. This will add to the body of knowledge in practice and provide directions for future research, policy development, and practical implementation.